WTO entry experience of China: Economic Developments (Journal of Economic Research & Business Administration, 2015)
The article considers the experience of China’s entry into the WTO as a developing country. The World Trade Organization (WTO) is a global organization that regulates international trade, the legal basis of which is in the wording of the GATT 1994, the General Agreement on Trade in Services (GATS), the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and a number of other legal documents. The main tool for regulating foreign trade is the customs tariff. To resolve discrepancies national foreign economic regulation, the WTO shall undertake the unification. The entry of certain countries in the WTO had a negative impact on their economic development and trade policy. China joined the WTO in December 2001 and the analysis of economic and trade policies of China shows that the country has managed to get more benefits from joining this organization, and made a leap forward in economic development. In connection with the entry of China into the WTO, rapidly increased the volume of exports has changed its structure is constantly growing share of products with high added value. China has also reduced import duties. China’s accession to the WTO has also contributed to accelerate the pace of implementation of the national policy of reform and opening up, China carried out over the past 20 years. China holds the leading position among the world’s largest recipients of foreign capital. In recent years, China has even moved into the first position.
Keywords: WTO; China’s entry into the WTO; trade policy; developing countries; the import duty